Magnetic Skyrmions - Ranjan Sahu, Dipti (IntechOpen, 2021)
Magnetic skyrmionics is an advanced and active research field, which involves fundamental physics, the creation of efficient next-generation high-density information devices, the formation and manipulation of nanometer-size skyrmions in devices, and the development of compatible materials at room temperature. The magnetic skyrmions found in magnetic materials exhibit spiral magnetism. This book presents a basic overview of magnetic skyrmions along with current research on magnetic skyrmions, emphasizing formation mechanisms and materials design strategies. This book is suitable for an interdisciplinary audience of undergraduates, graduates, engineers, scientists, and researchers in the development of the next generation of spintronic devices.